THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND MIE GAGA'S TIKTOK AI STORYTELLER CONTENT ON CONSUMER ATTITUDE - hasanah, ratih; Rahayu, Nadia Agustina (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
The development of internet technology is a link in the widespread use of social media which results in the wider community being able to easily obtain and share information about a company's products or services through Electronic Word of Mouth activities and content creation. TikTok is one of the most used social media in Indonesia, reaching 113 million users in 2023. It has various interesting features so that TikTok is used by content creators as a platform used to share informative and interactive content, and create Electronic Word of Mouth. Mie Gaga is a brand of instant noodle products produced by PT Jakarana Tama which is widely discussed by netizens due to the viral TikTok AI Storyteller Mie Gaga content uploaded by the @hizkianontiktok account on TikTok social media. This study aims to determine the influence and how much influence Electronic Word of Mouth and TikTok AI Storyteller Mie Gaga Content have on Consumer Attitudes. The method used in this study is quantitative method with descriptive research type. Sampling in this study was using a indikatorprobability sampling method with a type of purposive sampling to 400 respondents through an online questionnaire using Google Form. The results showed that Electronic Word of Mouth and TikTok AI Storyteller Mie Gaga Content had a positive and significant effect on Consumer Attitudes. This can be proven from the value of Fvalue > Ftable, which is 68.707 > 3.02 which means H0 is rejected and H1 is accepted. And based on the results of the coefficient of determination, which shows that Electronic Word of Mouth and TikTok AI Storyteller Mie Gaga Content have an influence of 25.7% on Consumer Attitudes.